Bullying against teachers and its implications on attitude towards the teaching profession – Study on a sample of teachers working in public schools in Qatar – - Abdelrahman, Mohamed Kamal Kamel; Hawi, Diala (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to reveal the extent that student bullying against teachers occurs in public schools in Qatar, as well as the different forms that it takes, and how it could predict teachers’ attitudes towards the teaching profession. To achieve these goals, the study followed the descriptive research methodology where among a sample of 155 male and female teachers, we found that teachers report being subjected to two different types of bullying: 20% of them reported being exposed to direct bullying (i.e., verbal or physical assaults), while 64.8% were exposed to indirect bullying (e.g., disrespect in the classroom). Moreover, the statistical results revealed that male teachers reported being indirectly bullied more than female teachers. Furthermore, both forms of reported bullying correlated with negative teachers’ attitudes toward the profession, but indirect bullying more strongly predicted these attitudes. The implications of the current study shed light on the consequences of bullying against teachers which have negative implications on the attitude towards the teaching profession.